. METHYLPREDNISOLONE EFFECTS ON SERUM BIOCHEMICAL FACTORS (CRP, PCT, IL-6, TNF-a) IN VIRAL PNEUMONIA: EFEKTI METILPREDNIZOLONA NA SERUMSKE BIOHEMIJSKE FAKTORE (CRP, PCT, IL-6, TNF-a) KOD VIRUSNE PNEUMONIJE - Zeng, Hongping; Zhu, Qi; Bai, Shaoyu; Liu, Jie; Ren, Dengjie; Chen, Xin (Journal of Medical Biochemistry, 2025)
Introduction: it was to demonstrate effects of methylprednisolone (MPS) and azithromycin treatment on serum biochemical factors and their impact on Serum Biochemical Factors (CRP, PCT, IL-6, TNF-α ) prognosis in patients with viral pneumonia (VP). Methods: 120 patients with VP admitted to our hospital were rolled into control (Ctrl), low-dose (80 mg MPS, L-MPS), medium-dose (500 mg MPS, M-MPS), and high-dose (1000 mg MPS, H-MPS) groups. The therapeutic efficacy of each group was evaluated. C-reactive protein (CRP), procalcitonin (PCT), and interleukin-6 (IL-6) were detected. Pulmonary function parameters were assessed using a pulmonary function testing device. Adverse reactions (ARs) such as fever, nausea, vomiting, and gastrointestinal bleeding post-treatment were recorded. Results: total effective rate (TER) post-treatment in Ctrl group was 60.00%, which was inferior to that in L-MPS group (76.67%), M-MPS group (90.00%), and H-MPS group (93.33%) (P<0.05). Disappearance time of CRP, PCT, IL-6, TNF-α, fever, cough, and X-ray infiltrates was reduced in L-MPS, M-MPS, and H-MPS groups relative to Ctrl group (P<0.05), while FVC, MMEF, and PEF were increased (P<0.05). Disappearance time of CRP, PCT, IL-6, TNF-α, fever, cough, and X-ray infiltrates in M-MPS and H-MPS groups was inferior to that in L-MPS group (P<0.05), while FVC, MMEF, and PEF were higher (P<0.05). Conclusion: medium-dose (80 mg) MPS combined with azithromycin greatly reduces inflammatory cytokine levels, shortens the time to clinical symptom relief, improves lung function and respiratory capacity, demonstrating significant efficacy in treating VP.